A new synonymy in the genus Macrocixius (Hemiptera: Fulgoromorpha: Cixiidae) - Orosz, András; Rédei, Dávid (Zootaxa, 2016)
Until recently the genus Macrocixius Matsumura, 1914 (Hemiptera: Fulgoromorpha: Cixiidae) contained two species: M. giganteus Matsumura, 1914 (the type species) and M. grossus Tsaur & Hsu, 1991. Two recent papers revised the genus within a short interval of time. Both Zhang & Chen (2013) and Orosz (2013) provided redescriptions of the genus and its two previously included species; Zhang & Chen (2013) described two new species from China; Orosz (2013) described five new species from Nepal, Taiwan, Vietnam, and Indonesia.